1992
DOI: 10.1111/j.1365-246x.1992.tb00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Static deformation of a uniform half-space due to a long dip-slip fault

Abstract: SUMMARY Closed‐form expressions for the displacements and stresses at an arbitrary point of a homogeneous, isotropic, perfectly elastic half‐space caused by a dip‐slip line source obtained earlier are integrated analytically to derive the elastic residual field due to a long dip‐slip fault of finite width. The results are valid for an arbitrary dip of the fault and for arbitrary receiver locations inside the medium. The variation of the displacement and stress field with the distance from the fault is studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 4 publications
0
31
0
Order By: Relevance
“…where K ij is the shear stress due to unit slip at the j-th cell given theoretically by RANI and SINGH (1992), u i is slip at the i-th cell, G is rigidity, and c is S-wave speed.…”
Section: Modelmentioning
confidence: 99%
“…where K ij is the shear stress due to unit slip at the j-th cell given theoretically by RANI and SINGH (1992), u i is slip at the i-th cell, G is rigidity, and c is S-wave speed.…”
Section: Modelmentioning
confidence: 99%
“…For this vertical cross section, we discretized the curved plate interface into 4400 line segments of nearly equal lengths of about 50 m. We confirmed that this length of line segment is sufficient to accurately model earthquake cycles with the distribution of frictional parameters shown later. Each line segment corresponds to a sub-fault; the slip response function K ij for this type of sub-fault was calculated by the analytic expression given by Rani and Singh (1992), which determines the stress change under the plane strain field due to the unit dip slip of each sub-fault in an elastic half space consisting of a Poisson solid with G = 30 GPa and V s = 3273 m/s. We assumed V pl = 5 cm/year for the plate subduction velocity.…”
Section: Configuration Of Model Plate Interface and Its Discretizationmentioning
confidence: 99%
“…Figure 4 shows static shear and normal stresses on the plate interface caused by the intraslab earthquakes in Table 1, where shear stress in slip direction and compression of normal stress are taken to be positive. These stresses are calculated by using analytical expressions for stresses due to dip slip (Rani and Singh, 1992). The average stress drop at the a − b < 0 region on the plate interface of the simulated interplate Fig.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…where K i j and J i j are static shear and normal stresses, respectively, at the ith cell due to unit slip on the jth cell and given theoretically by Rani and Singh (1992), u j is the slip amount on the jth cell, σ init i is the initial normal stress, P i and Q i are the shear and normal stresses caused by an intraslab earthquake, G is rigidity, and β is the S-wave speed of the medium. The third term on the right-hand side of (1) is introduced to represent shear-stress reduction during seismic slip.…”
Section: The Model For Repeating Interplate Earthquakesmentioning
confidence: 99%